EDUKASI PENGOLAHAN SAMPAH BOTOL PLASTIK MENJADI “POT” TANAMAN - Masnur Masnur; Muhammad Farid; Anggi Paramitha; Andi Bidasari Absharillah; Putri Handayani; Wulansari Ibrahim (Gapenas Publisher, 2021)
Until now, the participation of the community, in general, is only limited to waste disposal, but it has not yet reached the stage of waste management that can be useful again for the community. Therefore, waste management can take the form of disposing of waste or returning waste into valuable materials. This activity aims to provide educative training on how to carry out reforestation in narrow areas and an effort to increase public awareness in dealing with plastic waste that continues to grow. The method used is to educate the orphanage children, explain and understand waste, impacts, 3R materials, and practice processing plastic bottles into